Training on Making Liquid Organic Fertilizer (LOF) with P45 in Kandri Village - M. Raif Al Abrar; Aida Amalia; Laela Oktavia Nurul Hidayah; Tasya Tri Wahyuni; Manggala Putra Sahalana; Lenni Khotimah harahap (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The training on Liquid Organic Fertilizer (POC) production held in Kandri Village in collaboration with P45 aims to enhance the knowledge and skills of the local community in converting organic waste into valuable fertilizer. This activity involved active participation from the residents, focusing on the fermentation process of easily accessible organic materials. The results of this training indicated that the villagers are capable of independently producing POC, which has the potential to improve soil quality and agricultural yields in Kandri Village. Additionally, the training positively impacted community awareness regarding the importance of sustainable agriculture.